Women victims and survivors of the prostitution system. Outreach as a path to autonomy (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This article narrates the experience of the University Extension Project of the National University of La Pampa developed between 2022 and 2023, which focuses on participant observation as a methodological strategy for the research-extension approach to the territory. For this purpose, the experiential learning of the team is recovered in conjunction with the Association ‘Together To Be Free’, made up of women victims and survivors of the prostitution system. Although this was the first extension intervention with the organization, the link allowed us to think about different axes of work, including integrality, and thus take the first steps towards participatory research in the territory. The process of co-construction of the organization's problems and demands is explained, as well as the proposals forsolutions with the Association that collaborate with it's process of transformation towards autonomy and empowerment. In addition, the theoretical concepts that have been used in our project and actions are discussed.
Keywords: university extension; prostitution; integrality; abolitionism; participant observation